The Significance of Understanding Asbabun Nuzul and Munasabah on The Qur'an in the Post Truth Era - Pamuji, Zuri (Jurnal Studi Al-Qur'an, 2023)
The presence of the post-Truth Era impacts human life, both in the individual and in society. They are included in the religious aspect, where for Muslims, spiritual elements cannot be separated from the Qur'an. However, revealing the meaning of the Qur'an requires tools, including asbabun nuzul and munasabah. This study describes the significance of understanding asbabun nuzul and munasabah in the Post Truth Era. The research method uses descriptive qualitative with literature study. The study results a show that understanding asbabun nuzul and munasabah will be very helpful in adapting to the Post Truth Era, including terror in the name of religion because of mistakes in capturing the meaning of God's words.